2018
DOI: 10.1016/j.stem.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Daily Onset of Light and Darkness Differentially Controls Hematopoietic Stem Cell Differentiation and Maintenance

Abstract: Hematopoietic stem and progenitor cells (HSPCs) tightly couple maintenance of the bone marrow (BM) reservoir, including undifferentiated long-term repopulating hematopoietic stem cells (LT-HSCs), with intensive daily production of mature leukocytes and blood replenishment. We found two daily peaks of BM HSPC activity that are initiated by onset of light and darkness providing this coupling. Both peaks follow transient elevation of BM norepinephrine and TNF secretion, which temporarily increase HSPC reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 59 publications
6
90
1
11
Order By: Relevance
“…The circadian changes in the number of circulating HSPCs in PB were the subject of several excellent studies showing a peak in the early morning hours and a nadir at night [5][6][7][8][9][10][11][12][13]. This phenomenon has been attributed to diurnal changes in tonus of the vegetative nerves that innervate BM tissue as a result of external light and dark cycles [4,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The circadian changes in the number of circulating HSPCs in PB were the subject of several excellent studies showing a peak in the early morning hours and a nadir at night [5][6][7][8][9][10][11][12][13]. This phenomenon has been attributed to diurnal changes in tonus of the vegetative nerves that innervate BM tissue as a result of external light and dark cycles [4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another group has demonstrated that lightinduced norepinephrine and TNF secretion augments HSPC differentiation and increases vascular permeability, which releases HSPCs into PB in a circadian rhythm-dependent manner [6]. At the same time, darkness-induced TNF increases melatonin secretion, which drives renewal of HSPCs and diminishes vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations